Landslide Monitoring by Radar Permanent Scattered Remote Sensing Technique in Tangier - Hadek Ali; Wahbi Miriam; Hlal Mohammed; Maatouk Mustapha; Boulaassal Hakim; Elkharki Omar; Yazidi Alaoui Otman (E3S Web of Conferences)
In northern Morocco, local authorities in Tanger commonly map landslide susceptibility to support effective land use management and urban planning. The area's complex geology leads to significant land surface displacement, resulting in instability phenomena such as landslides and block falls. This study utilizes Persistent Scatterer Interferometric Synthetic Aperture Radar (PSinSAR) techniques with Sentinel-1 data in Interferometric Wide (IW) mode to evaluate ground deformation in Tanger from 2021 to 2023. We focused on mapping surface displacements in the radar line-of-sight direction by identifying persistent scatterers. The findings enhance the understanding and monitoring of slow deformation phenomena in the region, providing essential insights for land management and infrastructure planning.